All Days 1998
DOI: 10.2118/39551-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Breakthrough Numerical Simulation in Fractured Gas Reservoirs

Abstract: In the SiChuan gas fields of China, because of the complex geologic conditions, almost all the active water invasions appear to be water breakthrough along fractures. These seal the path of gas flowing in fractured gas reservoirs, as a result largely reducing the efficiency of gas production. Currently, it is very difficult to simulate such fracture water breakthrough using known fracture models (e.g, dual porosity, single permeability and dual porosity, dual permeability). In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the basis of the development of this water invasion physical simulation experimental technology, the understanding of water invasion mechanisms of fractured-porous gas reservoirs has been continuously improved and deepened, and the research achievements of various scholars can be synthesized: due to the hydrophilicity and low seepage resistance of fractures, under a certain pressure difference water breaks through rapidly along the larger fractures, resulting in gas in the rock being separated by fractures into several units and forming a water seal. After water invasion of a relatively highly permeable large fracture, under the action of capillary force [79,80] the water in the large fracture infiltrates into the matrix sealed by it. In the process of infiltration, in the narrow deformation of the pore throat and because of the Jamin effect, the continuous flow of gas will be blocked and some of the gas will be locked.…”
Section: Water Invasion Mechanism Of Fractured-porous Gas Reservoirmentioning
confidence: 99%
“…On the basis of the development of this water invasion physical simulation experimental technology, the understanding of water invasion mechanisms of fractured-porous gas reservoirs has been continuously improved and deepened, and the research achievements of various scholars can be synthesized: due to the hydrophilicity and low seepage resistance of fractures, under a certain pressure difference water breaks through rapidly along the larger fractures, resulting in gas in the rock being separated by fractures into several units and forming a water seal. After water invasion of a relatively highly permeable large fracture, under the action of capillary force [79,80] the water in the large fracture infiltrates into the matrix sealed by it. In the process of infiltration, in the narrow deformation of the pore throat and because of the Jamin effect, the continuous flow of gas will be blocked and some of the gas will be locked.…”
Section: Water Invasion Mechanism Of Fractured-porous Gas Reservoirmentioning
confidence: 99%
“…Numerical simulation shows that the strength and range of fracture development in the fault stretching segment are significantly greater than those in the translational and uplift segments, with better reservoir size and connectivity, and higher oil and gas accumulation levels. Research on ancient earthquakes and fracture mechanics shows that the sliding of strike–slip faults is usually episodic activity. There are significant differences in geometric styles of strike–slip faults active under different principal stress directions. This understanding can be applied to the study of the active stages of strike–slip faults, and their development patterns and evolution processes are usually studied using physical simulation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the fault underwent at least four stages of tectonic activity: the Middle Caledonian (III episode), Early Hercynian, Late Hercynian, and Indosinian periods. Although these studies have tried to determine the active stages of strike–slip faults in the cratons of the Tarim Basin, the criteria used are not uniform. , In addition, the longitudinal and planar evolution mechanisms and development patterns of strike–slip faults are relatively complex, and existing stage studies have not yet closely combined these two. Wang conducted a detailed analysis of the deformation patterns and activity of three main strike–slip faults in the study area using three-dimensional seismic small-scale slip distance strike–slip fault analysis technology, clarifying the structural style of “planar segmented connection and longitudinal layered deformation” of the strike–slip faults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in gas fields in Sichuan, China, nearly all active water-intrusion occurs aside fractures because of the complex geological conditions of the area. Zhang et al (2005) established a nonlinear coupled fluid simulation model suitable for bottom-water gas field development considering a nonlinear flow field and the matrix within fractures. Dynamic research on triple-medium carbonate reservoir water invasion, among other methods, is often based on experiments and core analyses.…”
Section: Introductionmentioning
confidence: 99%